Effect of Levosimendan on Acute Decompensated Right Heart Failure in Patients With Connective Tissue Disease-Associated Pulmonary Arterial Hypertension - Qu, Chao; Feng, Wei; Zhao, Qi; Liu, Qi; Luo, Xing; Wang, Gang; Sun, Meng; Yao, Zhibo; Sun, Yufei; Hou, Shenglong; Zhao, Chunyang; Zhang, Ruoxi; et al. (Frontiers in Medicine, 2022)
Aims Acute decompensated right heart failure (RHF) in chronic precapillary pulmonary hypertension is often typified by a swiftly progressive syndrome involving systemic congestion. This results from the impairment of the right ventricular filling and/or a reduction in the flow output of the right ventricle, which has been linked to a dismal prognosis of short duration. Despite this, there are limited therapeutic data regarding these acute incidents. This study examined the effect of levosimendan on acute decompensated RHF in patients with connective tissue disease-associated pulmonary arterial hypertension (CTD-PAH). Methods This retrospective study included 87 patients with confirmed CTD-PAH complicated acute decompensated RHF between November 2015 and April 2021. We collected biological, clinical, and demographic data, as well as therapy data, from patients with acute decompensated RHF who required levosimendan treatment in the cardiac care unit (CCU) for CTD-PAH. The patients were divided into two groups according to the levosimendan treatment. Patient information between the two groups was systematically compared in hospital and at follow-up. Results Oxygen saturation of mixed venose blood (SvO2), estimated glomerular filtration rate (eGFR), 24-h urine output, and tricuspid annular plane systolic excursion (TAPSE) were found to be considerably elevated in the levosimendan cohort compared with the control cohort. Patients in the levosimendan cohort exhibited considerably reduced levels of C-reactive protein (CRP), white blood cell (WBC), troponin I, creatinine, NT-proBNP, and RV diameter compared with those in the control cohort. A higher survival rate was observed in the levosimendan cohort. Conclusions Levosimendan treatment could effectively improve acute decompensated RHF and systemic hemodynamics in CTD-PAH patients, with positive effects on survival in hospital and can, therefore, be considered as an alternative treatment option for improving clinical short-term outcomes.